Ultrasound Imaging of Facial Vascular Neural Structures and Relevance to Aesthetic Injections: A Pictorial Essay - Wu, Wei-Ting; Chang, Ke-Vin; Chang, Hsiang-Chi; Kuan, Chen-Hsiang; Chen, Lan-Rong; Mezian, Kamal; Ricci, Vincenzo; Özçakar, Levent (Diagnostics (Basel, Switzerland), 2022)
The facial and submental regions are supplied by complicated neurovascular networks; therefore, facial aesthetic injections may be associated with serious adverse events such as skin necrosis and blindness. Pre-injection localization of neurovascular structures using high-resolution ultrasound can theoretically prevent unexpected complications. Therefore, a systematic protocol that focuses on these facial neurovascular structures is warranted. In this pictorial essay, we discuss the sonoanatomy of facial and submental neurovascular structures and its relevance to aesthetic injections. Moreover, we have highlighted the mechanisms underlying potential neurovascular injuries during aesthetic injections.
Keywords: safety; sonography; injection; rejuvenation; cosmetics